Odpowiedź :
[tex]a) \: 2(x - 8) + 4 - 11x = - 3(2x - 1) - (x + 4) \\ 2x - 16 + 4 - 11x = - 6x + 3 - x - 4 \\ 2x - 11x + 6x + x = - 4 - 3 - 4 \\ - 9x + 6x + x = - 7 - 4 \\ - 3x + x = - 11 \\ - 2 x = - 11 \: \: | \div ( - 2) \\ x = \frac{11}{ - 2} = - 5 \frac{1}{2} [/tex]
[tex]b) \: \frac{x + 2}{6} - \frac{2x - 5}{2} = \frac{4 - x}{3} \: \: | \times 6 \\ 6 \times \frac{x + 2}{6} - 6 \times \frac{2x - 5}{2} = 6 \times \frac{4 - x}{3} \\ x + 2 - 3(2x - 5) = 2(4 - x) \\ x + 2 - 6x + 15 = 8 - 2x \\ x - 6x + 2x = 8 - 2 - 15 \\ - 5x + 2x = 6 - 15 \\ - 3x = 9 \: \: | \div ( - 3) \\ x = 3[/tex]
[tex]c) \: \frac{2x + 1}{4} = \frac{x - 3}{2} \: \: | \times 4 \\ 4 \times \frac{2x + 1}{4} = 4 \times \frac{x - 3}{2} \\ 2x + 1 = 2(x - 3) \\ 2x + 1 = 2x - 6 \\ 2x - 2x = - 6 - 1 \\ 0 = - 7[/tex]
Równanie to może spełniać każda liczba.